Advancing Narcolepsy Advocacy: Bridging Patient Narratives and Systemic Change - BaHammam AS; Jesteadt L; Dhafar H; Sharafkhaneh A (Nature and Science of Sleep)
Ahmed Salem BaHammam,1,2 Lindsay Jesteadt,3,4 Hamza Dhafar,1,2 Amir Sharafkhaneh5,6 1Department of Medicine, College of Medicine, University Sleep Disorders Center, King Saud University, Riyadh, Saudi Arabia; 2The Strategic Technologies Program of the National Plan for Sciences and Technology and Innovation in the Kingdom of Saudi Arabia, Riyadh, Saudi Arabia; 3Sleep Consortium, Jupiter, FL, USA; 4Hypersomnia Foundation, Atlanta, GA, USA; 5Sleep Disorders and Research Center, Michael E. DeBakey VA Medical Center, Houston, TX, USA; 6Section of Pulmonary, Critical Care and Sleep Medicine, Department of Medicine, Baylor College of Medicine, Houston, TX, USACorrespondence: Ahmed Salem BaHammam, University Sleep Disorders Center, Department of Medicine, College of Medicine, King Saud University, Box 225503, Riyadh, 11324, Saudi Arabia, Email ashammam2@gmail.comAbstract: We introduce the Stigma-to-Structure Advocacy Framework, a novel, evidence-based model designed to transform narcolepsy advocacy by systematically bridging patient narratives with structural change. Narcolepsy remains a profoundly underdiagnosed and misunderstood neurological disorder, with persistent diagnostic delays and pervasive cultural stigma undermining patient well-being and access to care. Despite recent progress in awareness and support, advocacy efforts remain fragmented and insufficiently integrated with health policy, particularly in low- and middle-income countries. This perspective advances a strategic evolution of narcolepsy advocacy through the Stigma-to-Structure Advocacy Framework, which is anchored in three pillars: narrative-driven awareness, clinical system integration, and policy activation. Drawing on recent evidence, patient testimonies, and global case studies, we identify critical gaps in current advocacy models, such as limited representation of youth and marginalized populations, insufficient adaptation to cultural contexts, and the absence of standardized impact metrics. For example, ongoing diagnostic delays and entrenched cultural stigma continue to impede timely care and social inclusion for many individuals. We outline five priority actions for the next decade: developing outcome metrics, building culturally responsive advocacy hubs, integrating narcolepsy into rare disease registries, expanding peer mentoring networks, and reforming policy frameworks. By centering equity, digital inclusion, and cross-sector collaboration, this framework aims to dismantle entrenched barriers and promote timely diagnosis, effective care, and social inclusion for all individuals with narcolepsy. We conclude by calling for a globally coordinated, patient-powered movement that redefines advocacy as a driver of structural transformation in sleep medicine. Plain Language Summary: Narcolepsy remains significantly underdiagnosed worldwide, with patients waiting an average of 8-9 years for diagnosis while facing persistent stigma and limited support. Our perspective proposes a strategic evolution in narcolepsy advocacy, moving beyond awareness campaigns toward systemic change that can improve diagnosis times and patient outcomes.We introduce the “Stigma-to-Structure Advocacy Framework” with three interconnected pillars: narrative-driven awareness, clinical system integration, and policy activation. This approach bridges personal stories with healthcare system improvements and policy reforms.We identified five priority actions for the next decade:Developing standardized metrics to measure advocacy impactBuilding culturally responsive advocacy hubs that prioritize youth leadershipIntegrating narcolepsy into rare disease registries to improve data visibilityExpanding peer mentoring networks to support treatment adherenceReforming policy frameworks to recognize narcolepsy’s disabling impactThese priorities address critical gaps in current advocacy, particularly in low- and middle-income countries where limited specialist access, cultural misconceptions, and digital divides create barriers to care. By centering equity and cross-sector collaboration, this framework aims to transform narcolepsy advocacy into a globally coordinated movement that ensures timely diagnosis, effective treatment, and social inclusion for all affected individuals.Keywords: support group, stigma, peer support, diagnostic delay, health equity, patient empowerment